Hepatitis E virus infection prevalence among men who have sex with men involved in a hepatitis A virus outbreak in Italy - Spada, Enea (Blood Transfus, 2019)
BACKGROUND: The routes of hepatitis E virus (HEV) transmission have still not been fully clarified. Here, we evaluated the possibility of sexual transmission of HEV, which remains a highly disputed issue. MATERIALS AND METHODS: Hepatitis E virus sexual transmission risk was assessed by comparing the prevalence of HEV infection in a sample of 196 Italian men who have sex with men (MSM) involved in a multi-country hepatitis A virus (HAV) outbreak, and in 3,912 Italian male blood donors selected from the same regions and provinces as the MSM. Selection of study of participants was motivated by the fact that HEV prevalence among Italian blood donors has been found to vary enormously between different geographical areas. RESULTS: Anti-HEV IgG prevalence was 14.8% and 5.6% in blood donors and MSM, respectively. Adjusted anti-HEV IgG prevalence was significantly lower in MSM than in blood donors (odds ratio [OR], 0.40; 95% confidence interval [CI]: 0.22–0.75; p<0.01), among residents in northern (OR, 0.45; 95% CI: 0.37–0.55; p<0.01) and southern (OR, 0.45; 95% CI: 0.35–0.58; p <0.01) Italy than among residents in Central Italy, while the prevalence was significantly higher in participants over 50 years of age than in those under 50 years of age (OR, 1.83; 95% CI: 1.48–2.27; p<0.01). DISCUSSION: Our findings suggest that sexual intercourse does not have a relevant role in HEV transmission. In particular, sexual transmission of HEV is unlikely to influence the prevalence of HEV infection at population level.